2007
DOI: 10.3354/meps06970
|View full text |Cite
|
Sign up to set email alerts
|

Mapping plankton distribution in the Bay of Biscay during three consecutive spring surveys

Abstract: Nano-microplankton biomass, mesozooplankton biomass and hydrographic features were measured with mesoscale spatial resolution during 3 surveys in the Bay of Biscay between March and June 2004. Regions of high plankton biomass were associated with mesoscale physical structures. Generalized additive models (GAMs) based upon surface salinity, surface temperature and stratification of the water column explained 83% of the variability in nano-microplankton biomass distributions, 67% for small mesozooplankton, and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 47 publications
1
15
0
1
Order By: Relevance
“…GAM analyses were performed in two steps (Zarauz et al 2007, Silva et al 2014. First, GAMs were based on single explanatory variables to study the influence of each hydrographic parameter on the species abundance.…”
Section: Discussionmentioning
confidence: 99%
“…GAM analyses were performed in two steps (Zarauz et al 2007, Silva et al 2014. First, GAMs were based on single explanatory variables to study the influence of each hydrographic parameter on the species abundance.…”
Section: Discussionmentioning
confidence: 99%
“…First, it was hypothesised that food resource abundance and composition would greatly differ between spring and autumn, i.e. between seasons presenting different environmental conditions in temperate areas such as the Bay of Biscay (Villate et al 1997;Valdés and Moral 1998;Zarauz et al 2007). Moreover, survey data indicated that both springtime periods were different in terms of temperature and salinity patterns in particular, potentially leading to different food resource availability as well (i.e.…”
Section: Mesozooplanktonmentioning
confidence: 99%
“…between two consecutive springs), can be directly related to spatial and year-to-year variations in water temperature and salinity (Villate et al 1997, Zarauz et al 2007). Moreover, in the Bay of Biscay, the plumes of the Gironde and the Loire Rivers considerably influence the hydrological structure and the primary production on the continental shelf, all along the year (Planque et al 2004;Puillat et al 2004Puillat et al , 2006Loyer et al 2006;.…”
Section: Spatial Temporal and Size-related Variability Of Mesozooplamentioning
confidence: 99%
“…The ATC method, implemented as suggested by Bergeron (1983), was not focused on the spatial distribution or variations in zooplankton biomass, or its species composition, as usual in most zooplankton studies (e.g. Irigoien, 2004, 2007;Zarauz et al, 2007, for the Bay of Biscay). The specific activity of ATC in mesozooplankton communities provides a dynamic view of the overall productivity resulting from integrated metabolic activities controlled by environmental conditions.…”
Section: Occurred In 2003mentioning
confidence: 99%